Action of andiroba oil and permethrin on the central nervous and reproductive systems of Rhipicephalus sanguineus (Latreille, 1806) (Acari: Ixodidae) ticks females. A confocal study - Roma, Gislaine Cristina [UNESP]; Vendramini, Maria Cláudia Ramalho [UNESP]; Camargo-Mathias, Maria Izabel [UNESP]; Nunes, Pablo Henrique [UNESP]; de Faria, Adriano Uemura [UNESP]; Bechara, Gervásio Henrique [UNESP] (Elsevier, 2013)
Research for acaricides with lower toxicity and impact on the environment has been intensified. An alternative would be the use of natural compounds or of synthetic products in lower concentrations than the ones sold commercially. Thus, this study describes the action of andiroba seed oil on the nuclei of the ovary and synganglion cells of Rhipicephalus sanguineus, and presents an analysis of the nuclear morphology of the nervous system cells of this tick species when exposed to permethrin. The results obtained showed that, although no changes have been observed in the genetic material of the ovary cells exposed to the andiroba oil, this compound, as well as permethrin, has neurotoxic action on the females of this species. The damages caused to the physiology of the synganglion, due to the loss of integrity of the genetic material, would result in the impairment of the metabolism of other systems of R. sanguineus ticks. © 2013 Elsevier Ltd.
Keywords: Cell death; Natural product; Nuclear changes; Ovary; Synganglion; Synthetic product; andiroba oil; natural product; permethrin; unclassified drug; animal cell; cell nucleus; cell structure; confocal microscopy; controlled study; female; Ixodidae; nerve cell; neurotoxicity; nonhuman; ovary cell; reproductive toxicity; Rhipicephalus sanguineus; synganglion cell; Acari; Ixodida